High Performance Computing in Science and Engineering, Garching/Munich 2009 Transactions of the Fourth Joint HLRB and KONWIHR Review and Results Workshop, Dec. 8-9, 2009, Leibniz Supercomputing Centre, Garching/Munich, Germany - Wagner, Siegfried.; Steinmetz, Matthias.; Bode, Arndt.; M<U+00fc>ller, Markus Michael. (Springer Berlin Heidelberg, 2010)
This book presents selected project results obtained at the current High-Performance Computer in Bavaria (HLRB II). The research areas covered include Computer Sciences, Computational Fluid Dynamics, Astrophysics, High-Energy Physics, Geo Sciences, Condensed Matter Physics, Chemistry, and Bio Sciences. Thus, the book provides an overview of the broad range of applications requiring high-performance computers to solve challenging numerical problems. Each project description includes information on the respective scientific background, results achieved and methods used. The book also offers insights into the performance, scalability, and latest enhancements of the applications employed.